Dragonflies (Insecta: Odonata) As Heavy Metal Biological Indicator In Freshwater Ecosystem - Juma’at, Ahmad Hadri (2021)
Aquatic insects are a useful biological indicator in river biomonitoring. Therefore, a this study was conducted on Odonata larvae and their responses to the heavy metals exposure found in most rivers. Four species of dragonflies larvae, including a Coenagrionid family (Pseudagrion microcephalum, Pruinsoum fraseri and Ischnura senegalensis) and Platycnemidid (Copera marginipes), were collected from three different rivers in Kedah. Based on the Water Quality Index (WQI), all the three rivers were categorized as “moderately clean” (Class III) and all the environmental parameters showed significant spatial variation among the three rivers (F2,8= 7.90, P= 0.00) except temperature. Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) was used to analyze four heavy metals (Cd, Mn, Zn and Cd) concentrations in water, sediment and Odonata larvae. This metal analysis showed that all the metals were found in water, sediment, and the tissue of the Odonata larvae. However, most heavy metals concentrations were found greatest in Odonata tissue, specifically Mn and Zn. Analysis of variance (ANOVA) showed that all the concentration of metals in C. marginipes were statistically significant in all three rivers compared to the other two species studied. Further test using correlation and regression analysis found that the accumulation of Zn and Mn metals in water and sediment had significantly influenced the content of metals on both larvae, P. fraseri and C. marginipes, with a significant r-value at P < 0.05.